2014
DOI: 10.1172/jci68815
|View full text |Cite
|
Sign up to set email alerts
|

Metformin interferes with bile acid homeostasis through AMPK-FXR crosstalk

Abstract: The nuclear bile acid receptor farnesoid X receptor (FXR) is an important transcriptional regulator of bile acid, lipid, and glucose metabolism. FXR is highly expressed in the liver and intestine and controls the synthesis and enterohepatic circulation of bile acids. However, little is known about FXR-associated proteins that contribute to metabolic regulation. Here, we performed a mass spectrometry-based search for FXR-interacting proteins in human hepatoma cells and identified AMPK as a coregulator of FXR. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
118
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(126 citation statements)
references
References 52 publications
4
118
1
1
Order By: Relevance
“…However, after metformin treatment, TBAs and TC were both significantly reduced, suggesting that the secretion and excretion of BAs are promoted. A possible explanation for these results is that metformin interacts with and inhibits FXR thus increasing Cyp7a1 and bile acid transporters (Besp and Mrp2) [22]. Thus, our results suggest that administration of metformin in DM rat may increase bile flow favoring cholestasis.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…However, after metformin treatment, TBAs and TC were both significantly reduced, suggesting that the secretion and excretion of BAs are promoted. A possible explanation for these results is that metformin interacts with and inhibits FXR thus increasing Cyp7a1 and bile acid transporters (Besp and Mrp2) [22]. Thus, our results suggest that administration of metformin in DM rat may increase bile flow favoring cholestasis.…”
Section: Discussionmentioning
confidence: 51%
“…Besides, a former study showed that FXR was important in mediating the increase of FGF21 [3]. While another study showed that metformin activated AMPK can phosphorylate and inhibit FXR as well as its target proteins [22]. We hypothesized that there may exist other mechanisms in mediating metformin and FGF21 actions which is independent of FXR.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations